Active common-mode filter for capacitive-coupled isolated signalling - Angerer, Martin; März, Martin; Schwanninger, Raffael (Electronics Letters, 2020)
Capacitive coupling is a well-established principle in isolated signalling. A major challenge esp. in power electronics is common-mode transient immunity caused by the displacement currents at the coupling capacitors. Digital isolator integrated circuits (ICs) employ modulated signalling, the authors propose an active filter circuit to remove common-mode components from baseband signals. This allows for reliable data transmission during transients in power semiconductor control, AC-coupled RS-485 or transformer-less Ethernet. The filter structure is simple and consists of two current mirrors, one for positive transients, and one for the negative. A current on one differential signal line is 'mirrored' onto the other, common-mode currents are conducted to ground. Differential signals are minimally affected. The proposed filter is verified in simulation and experiment: Baseband signalling with 50 Mbps in presence of 30 kV/ ms burst transients is achieved using discrete semiconductors. Even better results are expected when monolithically embedding the filter in an integrated circuit.
CRIS-Team Scopus Importer:2020-02-04

Device Providing DC Short-Circuit Current - Gehring, Johannes; Schwanninger, Raffael; Kaiser, Julian; Wunder, Bernd; März, Martin (5th IEEE International Conference on DC Microgrids, ICDCM 2023, 2023)
This work introduces a short-circuit current device (SCCD) for low voltage DC grids. This device aims to provide a fault current for protection devices which require an overcurrent for a rather long period in order to trip, e.g. melting fuses, in grid installations where such currents are usually not available because of converter current limits and smaller grid-side capacitors.
Created from Fastlane, Scopus look-up
Keywords: DC microgrids; overcurrent; protection technology; selectivity; short-circuit power

Energy-Equivalent Inductance Measurement System - Gehring, Johannes; Nowak, Alexander; Schwanninger, Raffael; Wunder, Bernd; März, Martin (2023 IEEE Fifth International Conference on DC Microgrids (ICDCM), 2023)
In extensive DC grids and during DC charging of electric vehicles, line and filter inductances play a crucial role in the design of switching elements. The inductively stored energy significantly influences the energy dissipated in the switching elements during the switching process. Therefore, a measurement system for the energy-equivalent inductance is required. This paper presents a novel measurement principle and a measurement system based on it. Laboratory measurements demonstrate that the proposed measurement system provides accurate and reliable results, enabling precise estimation of the energy dissipation in switching elements and facilitating the selection of appropriate switching components.<br
Keywords: Inductance; Circuit breakers; Energy measurement; Switching loss; Switches; Inductance measurement; Energy storage; DC microgrids; DC charging; inductance measurement; circuit breaker; protection

Experimental Assessment of LVDC-Grid Stability Optimization using Circuit Simulation and Machine Learning - Schwanninger, Raffael; Roeder, Georg; Wienzek, Peter; Lavery, Melanie; Wunder, Bernd; Schellenberger, Martin; Lorentz, Vincent; März, Martin (2023 IEEE Fifth International Conference on DC Microgrids, 2023)
Low-voltage direct current networks play a central role in the realization of a sustainable, resilient energy supply. The stabilization of the networks during design and operation of the grids is a particular challenge since more and more components must be included in the stability analysis and control. Therefore, it is desirable to increasingly apply automated computations and artificial intelligence techniques for stability optimization. This paper describes the investigations for the experimental validation of a new approach for stability optimization, which can be applied in regular grid operation. A direct current network is mapped into a digital twin for automated computation of stability states. A classification model establishes the relationship between the network input parameters and the stability states, so that improved network parameter settings can be determined with a novel optimization method. A novel impedance measurement based on pseudorandom binary sequences (PRBS) enables precise characterization of grid components and continuous stability monitoring. Following the component characterization, the digital twin model is transferred and validated on a direct current network testbed and at the example of adjusting characteristic droop control curves.<br
Keywords: Low voltage; Microgrids; Power system stability; Stability analysis; Circuit stability; Digital twins; Optimization; Low-Voltage DC microgrid; grid stability; machine learning; random forest; surrogate model; cognitive power electronics

Exploration of Use-Case-Dependent Modeling Approach for Distributed DC-Grids - Lavery, Melanie; Schwanninger, Raffael; März, Martin (2024 IEEE Sixth International Conference on DC Microgrids (ICDCM), 2024)
In this paper, the previously described Use-Case-Dependent Modeling Approach is evaluated and its usefulness for grid simulation is explored. One of the main merits of the approach is its application in automated system analysis. Previous results also suggest a reduced usage of computing resources. This however has not yet been systematically tested and properly verified. Therefore, to inspect the validity of this approach, the methodology is explained and simulation results are compared to measurements of the modeled DC system. It is shown that the grid models adequately represent the system's behavior and the simulation results can therefore be used for system analysis. Discrepancies can be explained by an insufficient modeling of the measured system's damping elements. These differences are however small enough to be mitigated by usually applied error margins, especially for system stability analysis. Although more work is required for full verification, the validity and versatility of the approach is demonstrate

Holistic Concept for Simulation-based Planning and Design of Hybrid AC/DC Energy Grids for Production Systems - Barth, Martin; Gutwald, Benjamin; Russwurm, Eva; Lavery, Melanie; Schwanninger, Raffael; März, Martin; Franke, Jörg (Simulation Notes Europe, 2024)
This paper proposes a simulation-based planning concept and a simulation architecture for the design of hybrid AC/DC grids, which have the potential to significantly contribute to the energy transition. The paper discusses the lack of knowledge for the design of these grids, and presents a simulation approach to efficiently design hybrid grids and analyze them based on an electrical simulation. The authors also address the need to include process-specific characteristics in the planning and analysis of the electrical network, which is why common simulation tools for production processes are included in the approach. This allows economical, ecological, safety-relevant and technical aspects to be integrated into the planning process. The proposed concept is further discussed and planned for validation on the basis of a demonstrator currently under construction.<br

How to choose the optimal gan-hemt for a hard switching application – a guide - Dobusch, Julian; Schwanninger, Raffael; Kohlhepp, Benedikt; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2021)
Modern GaN-HEMTs offer beneficial advantages over traditional Si-MOSFETs. GaN-HEMTs exhibit much lower stored charge (QOSS ) while providing identical conduction losses (RDS,On ). However, choosing the right switch is not straight forward and the non-linear relation of voltage and charge has to be taken into account. This paper presents a guide on how to select the right switch to minimize conduction and switching losses considering the crucial influence of all switches on the switching losses.
CRIS-Team Scopus Importer:2021-11-05

Hybrid Modulation Scheme for CLLC Resonant Converter with Ultra-Wide Voltage Range for V2G Applications - Yang, Xiaotian; Wunder, Bernd; Yin, Shi; Schwanninger, Raffael; März, Martin; Lorentz, Vincent (2024 IEEE 6th International Conference on Direct Current Microgrids, ICDCM 2024, 2024)
In this paper, a hybrid modulation scheme consisting of phase-shift modulation (PSM) and pulse-frequency modulation (PFM) for a CLLC resonant converter for vehicle charging applications in DC Microgrids is proposed. To increase the operating range of the converter, an iterative design process of the converter is introduced. PSM, as a conventional alternative to PFM, can be used to further increase the operating range and improve the efficiency at light-load conditions. Since the converter in vehicle-to-grid (V2G) applications oftentimes operates under light-load conditions, implementing this hybrid modulation scheme can increase the efficiency dramatically. A novel idea of mode switching is also proposed in the paper to ensure smooth mode transitions. The working principle of this modulation scheme and the efficiency analysis were investigated in PLECS.
CRIS-Team Scopus Importer:2024-10-11
Keywords: CLLC; DC Charging; DC Microgrids; Efficiency Improvement; Hybrid Modulation; Mode Switching; V2G

Hybrid Modulation Scheme for CLLC Resonant Converter with Ultra-wide Voltage Range in V2G Mode - Yang, Xiaotian; Wunder, Bernd; Yin, Shi; Schwanninger, Raffael; März, Martin; Lorentz, Vincent (IEEE International Conference on DC Microgrids (ICDCM 2024), 2024)

Introduction of a Self-Stabilizing Decentralized Energy Management System for Undersupplied EV Charging Parks - Schwanninger, Raffael; Friedrich, Juliane; Drexler, Kilian; Lavery, Melanie; März, Martin (IEEE Open Journal of Power Electronics, 2025)
In this paper, a decentralized self-stabilizing Energy Management System for undersupplied EV charging parks is presented. This undersupply is due to the maximum power demand from all charging stations connected to a common DC grid being larger than the maximum infeed power from AC mains. The EMS allows easy addition of additional participants such as chargers, or storage systems, into the common DC grid. To assure grid stability, this decentralization necessitates adjustments to the control structure of connected power converters. To show the self-stabilizing effect, a simulation model based on real-world charging park data evaluates the EMS under varying levels of undersupply and storage capacity. The findings are further verified by implementation of the EMS into actual power converters and their stability assessment through impedance measurement. <br
Keywords: Energy management; Batteries; Power system stability; Microgrids; Power electronics; Load shedding; Power demand; State of charge; Energy management systems; Voltage control

Investigation of a Decentralized Energy Management System for Undersupplied EV Charging Parks - Schwanninger, Raffael; Friedrich, Juliane; Lavery, Melanie; März, Martin (2024 IEEE Sixth International Conference on DC Microgrids (ICDCM), 2024)
In this paper, an energy management system (EMS) for undersupplied EV charging parks is presented. This undersupply is due to the maximum power demand for all charging stations connected to a common DC grid being larger than the maximum in feed power from AC mains. The EMS is completely decentralized and therefore allows easy addition of additional participants like chargers, AC/DC converters or storage systems into the common DC grid. This decentralization requires changes to the control structure of the connected power converters. These changes are evaluated for their effect on the stability of the whole grid. To investigate the proposed EMS, a simulation model based on real world charging park data is set up. The model is then used to evaluate the EMS for different degrees of undersupply and buffer storage. The findings are evaluated for different performance indicators to show the trade off between peak power shaving, installed storage and the charging of EV

Investigation of Use-Case-Dependent Modeling Approach for Switched-Mode Power Converters for LVDC Grid Evaluation - Lavery, Melanie; Schwanninger, Raffael; März, Martin (PCIM Europe Conference Proceedings, 2024)
In this paper, the methodology for creating models of power electronic converters based on a recently presented simulation approach for LVDC grids is discussed. This analysis-use-case dependent modeling approach defines three complexity levels for the component models to be used for specific evaluation cases. The theoretical basics and conventions for the three modeling levels of switched-mode converters are presented in this paper. The converter components are collated into functionally distinct subsystems to explore the modeling conventions and analytical descriptions. The parameters required to create models of buck, boost and buck-boost converters are derived and explained. Finally the model behavior for the three model levels is briefly studied and discussed. Based on this in-depth description, a detailed investigation of model accuracy and its implications on the results of the grid simulation can be carried out.
CRIS-Team Scopus Importer:2024-09-13

Method for Detection and Limitation of Short-Circuit Currents for Semiconductor Circuit Breakers in LVDC Grids Using a Pre-Saturated Inductor - Gehring, Johannes; Schwanninger, Raffael; Nowak, Alexander; Wunder, Bernd; Lorentz, Vincent; März, Martin (IEEE Open Journal of Power Electronics, 2025)
This paper introduces an innovative non-destructive device designed to detect and limit short-circuit currents in LVDC grids. The proposed solution utilizes a transformer fully saturated by a permanent magnet during normal operation. When a short-circuit condition occurs, the transformer desaturates, reducing the rise in current and triggering the detection and protection mechanism. The structure and functionality of the device, along with the design criteria, are discussed. Additionally, optimization measures are presented, examined, and validated. Experimental results from the advanced device prototype demonstrate its effectiveness in detecting and limiting overcurrents. The device features a stable tripping threshold and can safely and reliably interrupt even low time constant capacitive short-circuits. This hardware-based detection solution is ideally suited for installation in a semiconductor circuit breaker.
CRIS-Team Scopus Importer:2025-04-11
Keywords: current measurement; DC circuit breakers; DC power systems; fault current limiters; overcurrent protection; protection; short circuit currents

Modelling and Design of a Droop-Based Cascaded Controller for LLC Resonant Converter - Yang, Xiaotian; Pohlenz, Stephan; Schwanninger, Raffael; Schleippmann, Nico; Wunder, Bernd; März, Martin (2023 IEEE Fifth International Conference on DC Microgrids, 2023)
This paper proposes a digital cascaded control strategy for integrating an LLC resonant converter into a DC Microgrid. The designed control scheme is particularly suitable for battery storage applications in discharging mode. The outer loop of the cascaded controller is a droop controller which provides the reference current according to the DC grid voltage. The inner loop regulates the current according to the reference by pulse frequency modulation (PFM). A seventh-order state-space model based on first harmonic approximation (FHA) and extended describing function (EDF) was built to assist the controller design. The proposed control scheme is validated for both buck and boost operation mode in the PLECS simulation environment.<br
Keywords: Microgrids; Resonant converters; Switches; Harmonic analysis; State-space methods; Voltage control; Time-domain analysis; Droop Control; Cascaded Control; LLC Resonant Converter; DC Microgrid

Novel approach to model gan-hemt capacitances using sigmoid functions - Dobusch, Julian; Schwanninger, Raffael; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2021)
Simulation of circuits is of high importance in the design process of power electronic devices. Modeling the nonlinear behavior of switches can be challenging, especially regarding the parasitic capacitances. They, however, play a crucial role in determining switching losses as well as voltage slopes of soft switched converters. This paper presents an approach to improve the SPICE model of a GaN-HEMT by modeling the nonlinear datasheet slope of the switch capacitances with continuous sigmoid functions resulting in better accordance between datasheet and simulation model.
CRIS-Team Scopus Importer:2021-11-05

Novel compensation scheme for low dynamic converters in droop-controlled DC grids - Gehring, Johannes; Gosses, Kilian; Schwanninger, Raffael; Zeilmann, Bernd; Wunder, Bernd (2022 IEEE 13th International Symposium on Power Electronics for Distributed Generation Systems, PEDG 2022, 2022)
Droop-control is a common method for DC microgrids to realize grid stability and in-feed management. This work presents a novel compensation scheme that enables the grid integration of very low-dynamic converters without integrated droop control using other high-dynamic converters present in the grid. A wider range of converters can thus be used in DC microgrids. The compensation scheme is validated with a simulation of an existing DC grid.
CRIS-Team Scopus Importer:2022-12-02
Keywords: DC grid modelling; DC microgrids; droop-control; grid control

Novel Device for Fast Detection and Limitation of Short-Circuit Currents in LVDC Grids - Gehring, Johannes; Wunder, Bernd; Schwanninger, Raffael; März, Martin; Lorentz, Vincent R. H. (2024 IEEE Sixth International Conference on DC Microgrids (ICDCM), 2024)
This paper introduces a novel non-destructive device for detecting and limiting short-circuit currents in LVDC grids. The proposed solution is based on the concept of using a transformer fully saturated by a permanent magnet during normal operation. When a short circuit condition occurs, the transformer desaturates, triggering the detection and protection mechanism. The function and structure of the unit as well as design criteria are explained. Experimental results demonstrate the effectiveness of the device in detecting and limiting overcurrents. This hardware-based detection solution is particularly suitable for being installed in a semiconductor circuit breaker rated up to but not limited to 100
Keywords: Limiting; Short-circuit currents; Circuit breakers; Microgrids; Permanent magnets; Circuit faults; Protection

Output Impedance Measurement of Digitally Controlled Power Converters in LVDC-Grids - Schwanninger, Raffael; Schmitt, Daniel; Lavery, Melanie; Wunder, Bernd; März, Martin (2024 IEEE Sixth International Conference on DC Microgrids (ICDCM), 2024)
Due to the increase in possible sector couplings to local low voltage DC grids, the amount of controlled infeed converters connected to the grids increases. For these grids to remain stable, proper system analysis is required. While simulation of these systems is possible, the final setup requires measurements. In this paper, the problem of output impedance measurement of digitally controlled power converters, which make up the majority of infeed converters in medium to high power LVDC grids, is discussed. Digital control leads to several requirements regarding the test signals used to measure the converters. Due to the nonlinearity of certain power converter types, the measurements required for a full description of the power converter typically need to be taken for a variety of loads and grid voltages. Wide bandwidth measurements can be used to reduce the overall measurement time. These wide bandwidth measurements require further investigation regarding signal amplitude, which is presented in this pape

Reinforcement Learning Strategies for Parameter Design of Bidirectional Cllc Resonant Converters With Ultrawide Voltage Range - Yang, Xiaotian; Kruse, Georg; Schwanninger, Raffael; Coelho, Rodrigo; Wunder, Bernd; Rosskopf, Andreas; Lorentz, Vincent; März, Martin (2024 IEEE Design Methodologies Conference (DMC), 2024)
In this paper, a design methodology of the resonant tank for a bidirectional CLLC resonant converter based on massively parallelized circuit simulations is proposed to achieve ultrawide input/output voltage range. A simplified closed-loop model of the CLLC converter with variable circuit parameters is built. To investigate potential configurations of the circuit parameters, various sampling methods and optimization techniques are used to generate diverse sets of parameters: Grid Search (GS), Tree-structured Parzen Estimator (TPE), Covariance-Matrix Adaptation Evolution Strategy (CMA-ES), standard Reinforcement Learning (RL), Diversity-driven Reinforcement Learning (DdRL). Appropriate criteria have been added to greatly narrow down the plausible sampled design configurations which can be used for further detailed analysis. Together with the conventional design method following the design guideline, the design performances are analyzed and compared. The sampling results indicate the RL-based algorithms can obtain the comparable number of effective designs as GS and have much better diversity at the same time, which demonstrates the RL-based design methods can effectively help power electronic engineers design the resonant tank parameters of the CLLC converte

Simulation-based planning and design of hybrid AC/DC energy grids for production systems: a holistic approach - Barth, Martin; Gutwald, Benjamin; Russwurm, Eva; Franke, Jörg; Lavery, Melanie; Schwanninger, Raffael; März, Martin (20. ASIM Fachtagung Simulation in Produktion und Logistik 2023, 2023)
This paper proposes a simulation-based planning concept and a simulation architecture for the design of hybrid AC/DC grids, which have the potential to significantly contribute to the energy transition. The paper discusses the lack of knowledge in the market for the design of these grids, and presents a simulation approach to efficiently assemble hybrid networks and analyse them based on an electrical simulation. The authors also address the need to include process-specific characteristics in the planning and analysis of the electrical network, which is why common simulation tools for production processes are included in the approach. This allows economic, ecological, safety-relevant and technical aspects to be integrated into the planning process. The proposed concept is further discussed and planned for validation on the basis of a demonstrator currently under construction.
Keywords: Produktion; Logistik; Simulation

Switching loss estimation of gan-hemts by thermal measurement procedure - Kohlhepp, Benedikt; Kübrich, Daniel; Schwanninger, Raffael; Dürbaum, Thomas (PCIM Europe Conference Proceedings, 2021)
Modern semiconductors like GaN and SiC enable high efficient power conversion and provide superior switching behavior. For achieving high efficient converter designs, reliable data concerning losses is vital. Due to the high voltage and current slew rates during switching, the conventional double pulse test cannot be beneficially applied when using GaN to gain results concerning switching losses. Thus, this paper proposes a novel procedure to estimate switching losses by means of thermal measurements. A characterization of the test setup using DC currents links the occurring device temperatures during switching operation to power losses. First measurements prove the applicability of the procedure to a 100 V GaN device.
CRIS-Team Scopus Importer:2021-11-05

The PROGRESSUS project - Highly efficient and trustworthy electronics, components and systems for the next generation energy supply infrastructure - Schmidt, Holger; Gutierrez, Antonio Javier Cabrera; Romani, Aldo; Crescentini, Marco; Borger, Kris; Chacon, Raphael; Forster, Adrian; Schwanninger, Raffael; Eberle, Thomas; März, Martin (2023 AEIT International Conference on Electrical and Electronic Technologies for Automotive (AEIT AUTOMOTIVE), 2023)

Use-Case-Dependent Modeling Approach for Analysis of Distributed DC Grids - Lavery, Melanie; Schwanninger, Raffael; März, Martin (IEEE Open Journal of Power Electronics, 2025)
This paper investigates a generalized modeling approach for DC grid components by applying it to the simulation and analysis of a comprehensive DC grid system. The approach has been introduced in previous works, which discussed the overall objectives, scope of application and the modeling methodology for switched-mode power converters. However, a systematic validation of the system model’s behavior remains outstanding. The research presented in this work addresses this gap by detailing and applying the methodology and comparing simulation results with measurements from a DC system. The findings reveal that the grid models adequately represent the system’s actual behavior and making the simulation results useful for simulation-based system analysis. Discrepancies arise from an insufficient modeling of the system’s damping elements. These differences however fall within acceptable error margins, especially in the context of system stability analysis. Despite the need for further verification, this paper demonstrates the approach’s potential and facilitating the development of versatile component libraries and hence design tools for DC systems.
CRIS-Team Scopus Importer:2025-01-31
Keywords: DC Grid Simulation and Design; Distributed DC Grids; Impedance Based Analysis; Power Converter Modeling; Short Circuit Analysis

Use-Case- Dependent Modeling Approach for Computer Simulation of Hybrid AC-DC Grids - Lavery, Melanie; Schwanninger, Raffael; März, Martin (2023 IEEE Fifth International Conference on DC Microgrids, 2023)
An analysis-use-case dependent modeling approach for the computer simulation of hybrid AC-DC grids employing component models with varying degrees of complexity is presented. Three different component model complexity levels for three different component functionality groups and three different use cases are defined. The component modeling is based on analytical averaged descriptions of the converter behavior and introduces a standardized model interface. The proposed merits of this approach are faster simulation times and easier result evaluation making this approach suitable for automated grid simulation and assisted layout evaluation. This makes a technical and economical design evaluation of AC- DC grids much more feasible. Furthermore, manufacturers of grid components could use this design approach to develop models with unified interface ports to be used in DC grid model component libraries. The optimization of computing time for different simulation run times is tested and presented using a simulation tool developed using this approach.<br
Keywords: Analytical models; Computational modeling; Biological system modeling; Computer simulation; Microgrids; Complexity theory; Optimization; DC component modeling; LVDC-Simulation; DC for industrial applications; Hybrid LVDC grids